American Indian Family Caregivers' Experiences with Helping Elders - Jervis, Lori L. (2010)
Abstract In recent years, a vast literature has accumulated on the negative effects on family caregivers of providing care to elders, while relatively little research has explored caregiving as a positive experience. Only a handful of studies have examined any aspect of informal caregiving among American Indians. This mixed methods study explores the negative and positive aspects of providing elder care among 19 northern plains American Indian family members. These caregivers described low levels of burden and high levels of reward, attributable to cultural attitudes toward elders and caregiving, collective care provision, strong reciprocal relationships with elders, enjoyment of elders, and relatively low levels of care provision. Caregiving manifested as part of a complex exchange of assistance rather than a unidirectional provision of assistance from the family member to the elder. That caregiving emerged as such an overwhelmingly positive experience in a community faced with poverty, alcohol disorders, trauma, and cultural traumatization is testimony to the important roles that elders often continue to play in these communities.